Oral health related knowledge in a disadvantaged population group - Dr Shalinie King; Dr Liliana Laranjo; Professor Benjamin Smith (Elsevier, 2023)
Aim or Purpose: Oral health is a key indicator of overall health and those from disadvantaged groups are disproportionately affected by poor oral health. This study aims to investigate oral health related knowledge and perceptions in a socially and culturally diverse population of Australian adults visiting a public dental clinic in Western Sydney in order to design and implement strategies to reduce disparities in oral health status. Materials and Methods: A qualitative study where semi-structured interviews were used to collect information on oral health related knowledge, perceptions and attitudes. The study was approved by the Western Sydney Local Health District Human Research Ethics Committee (protocol number: 2021/ETH12053) A sample of 21 participants attending a public dental clinic in Western Sydney was recruited between March 2022-September 2022. Interviews were analysed using a thematic approach. Results: Participants had a mean age of 68.1 (SD14.6) years, 40% female, and 64% born in Australia. Themes identified included 1) poor attitudes and perceptions about oral health, 2) limited oral health related knowledge and education and 3) barriers and enablers to maintaining good oral health. Conclusions: Overall there was a lack of agency and low prioritisation of oral health, limited knowledge about the causes and consequences of poor oral health, including limited access to oral health education. In a socially and culturally diverse population of Australian adults, strategies are required to better empower individuals to manage their oral health, which in turn will increase the prioritisation of oral health care and help overcome the barriers to accessing care.